Relevant efficiency enhancement of emerging Cu2MnSnS4 thin film solar cells by low temperature annealing. (June 2017) - Le Donne, A.; Marchionna, S.; Acciarri, M.; Cernuschi, F.; Binetti, S.
Graphical abstract: Highlights: Cu2 MnSnS4 thin films were grown by sulfurization of evaporated precursors. A comprehensive characterization of both CMTS layers and PV devices is discussed. CMTS PV devices were annealed at temperatures between 200 and 275 °C for 40′. The modification of material properties upon annealing was investigated. Literature record efficiency of 0.83% was reached upon 40′ annealing at 225 °C. Abstract: Earth abundant and low cost Cu2 MnSnS4 (CMTS) thin films were grown by a two-step vacuum approach: metal precursor stacks grown by thermal evaporation were heat treated in elemental sulfur vapors. Cu-poor/Mn-rich CMTS samples with large grain size and good layer compactness were obtained by sulfurization at 585 °C with an initial step at 115 °C to enhance the metal intermixing. They were primarily tested by Energy Dispersive Spectroscopy, micro-Raman and Photoluminescence. Then, solar cells based on them were realized and tested, showing enhanced performance with respect to a previous study (efficiency 0.5%, open-circuit voltage 302 mV, short-circuit current density 4.6 mA/cm 2, fill factor 36%). A 40 min post-deposition annealing in air at 225 °C significantly improved the performance of these emerging PV devices (efficiency 0.83%, open-circuit voltage 354 mV, short-circuit current density 5.8 mA/cm 2, fill factor 40%). The beneficial effects of the low temperature annealing were investigated, in terms both of material properties and PV device performance modification.